Assessing the Taxonomic Status of the Gray Brocket Mazama simplicicornis argentina Lönnberg, 1919 (Artiodactyla: Cervidae) - Sandoval, Eluzai Dinai Pinto [UNESP]; Vacari, Gabrielle Queiroz [UNESP]; Juliá, Juan Pablo; González, Susana; Vozdova, Miluse; Cernohorska, Halina; Kubickova, Svatava; Kalthoff, Daniela C.; Duarte, José Mauricio Barbanti [UNESP] (My University, 2023)
Mazama simplicicornis argentina is the name that was given to describe a gray brocket collected by Lönberg in 1919 in the central Chaco region of Argentina. Subsequent authors, based on morphological similarities, considered this name to be a synonym for the species Subulo gouazoubira Fischer, 1814 from Paraguay. In the absence of genetic analyses to compare the Argentinian and Paraguayan gray brockets, we aimed to clarify the taxonomy of M. simplicicornis argentina through an integrative assessment using morphological, cytogenetical, and molecular data from its holotype and a current topotype. Qualitative skull features and cranio-morphometric results of M. simplicicornis argentina showed a great similarity with the S. gouazoubira neotype characters. The diploid chromosome number of M. simplicicornis argentina topotype corresponded with the karyotypical pattern of S. gouazoubira with 2n = 70 and FN = 70, showing a great similarity in all classic and molecular cytogenetic results and revealing the homologies between karyotypes. The phylogenetic analysis of mitochondrial genes used in this study (concatenated partial ND5 and Cytb gene) allocated the M. simplicicornis argentina specimens in the monophyletic clade of S. gouazoubira with a branch value of 100%. These results show that there is no discontinuity between the Argentinian and Paraguayan gray brockets. Therefore, the individuals originally described as M. simplicicornis argentina should be recognized as S. gouazoubira.
Keywords: Animal cytogenetic; Cervidae; Gray brocket; Mitochondrial DNA; Morphology